Pharmacists' perspectives on traditional, complementary, and integrative medicine in Japan with special reference to Kampo medicines: an internet survey with preliminary interviews - Yoshiharu Motoo; Keiko Yukawa; Kazuho Hisamura; Ichiro Arai (BMC, 2022)
Abstract Background Pharmacists guide patients in their use of traditional, complementary, and integrative medicine (TCIM). The present study aimed to evaluate the opinions of Japanese pharmacists regarding TCIM, and to evaluate the usability of the evidence-based Japanese Integrative Medicine (eJIM) website from the pharmacists' point of view. Methods We conducted a two-stage, mixed-method study using interviews and an internet-based survey. In-person interviews were conducted with 20 pharmacists working in hospitals, dispensing pharmacies, or retail pharmacies. We analyzed their perspectives on TCIM and the usability of the eJIM. Based on the interviews, questionnaires for an internet survey conducted in February 2019 were developed. Results In the interviews, 55% of pharmacists acknowledged TCIM as a supportive measure for modern medicine, and 45% responded that TCIM was efficacious. However, pharmacists' evaluation levels of Kampo medicine were high, whereas pharmacists' attitudes towards dietary supplements were primarily negative. There have been various proposals to improve the eJIM, such as highlighting important information and providing more specific information on TCIM in Japan. An internet survey of 365 pharmacists showed that 67.4% were consulted by patients regarding TCIM. Of these TCIM, pharmacists' evaluation levels of Kampo medicines were high. Only 5% of the respondents had visited the eJIM website prior to the survey, and the overall usability score of each web page was high. Conclusions Kampo medicines and dietary supplements are common TCIMs that pharmacists use or advise on in Japan. Pharmacists' evaluation levels of Kampo medicine were high, whereas pharmacists' attitudes towards dietary supplements were generally negative.